Polymers for application in organic solar cells: Bithiophene can work better than thienothiophene when coupled to benzodithiophene. Issue 11 (22nd December 2015) - Parenti, Francesca; Ricciardi, Rosa; Diana, Rosita; Morvillo, Pasquale; Fontanesi, Claudio; Tassinari, Francesco; Schenetti, Luisa; Minarini, Carla; Mucci, Adele
ABSTRACT: The synthesis and characterization of two low band gap copolymers (P1 andP2 ) incorporating benzo[1, 2‐ b :4, 5‐ b ']dithiophene unit substituted with octylsulfanylthienyl groups (OSBT) are here reported. These materials, designed to be employed in polymer solar cells (PSCs), were obtained from alternating OSBT and bithiophene (P1 ) or thienothiophene (P2 ) units. Their structural electrochemical and photophysical properties were investigated. They are thermally stable and soluble in organic solvents from which they easily form films. They also form π‐stacks in solution, in film and display a moderate solvatochromism. These polymers were tested with [70]PCBM in bulk‐heterojunction (BHJ) PSCs where they act as donor materials and [70]PCBM is the electron acceptor. The best device, obtained using a 1:3 weight ratio for theP1 :[70]PCBM blend, shows a PCE around 1.5%. A broad response from 350 to 700 nm is also observed in the external quantum efficiency (EQE) curves, wider forP1 with respect toP2 . © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 1603–1614 Abstract : Thienothienyl and bithienyl units were copolymerized with a benzodithiophene substituted with alkylsulfanylthienyl groups and the obtained copolymers were tested in combination with [70]PCBM as photoactive layers in bulk‐heterojunction polymer solar cells, with the aim to compare the efficiency of the final devices.